Polydatin Counteracts 5-Fluorouracil Resistance by Enhancing Apoptosis via Calcium Influx in Colon Cancer - Hyocheol Bae; Woonghee Lee; Jisoo Song; Taeyeon Hong; Myung Hyun Kim; Jiyeon Ham; Gwonhwa Song; Whasun Lim (MDPI AG, 2021)
Colon cancer is a disease with a high prevalence rate worldwide, and for its treatment, a 5-fluorouracil (5-FU)-based chemotherapeutic strategy is generally used. However, conventional anticancer agents have some limitations, including the development of drug resistance. Therefore, there has recently been a demand for the improvement of antitumor agents using natural products with low side effects and high efficacy. Polydatin is a natural active compound extracted from an annual plant, and widely known for its anticancer effects in diverse types of cancer. However, it is still not clearly understood how polydatin ameliorates several drawbacks of standard anticancer drugs by reinforcing the chemosensitivity against 5-FU, and neither are the intrinsic mechanisms behind this process. In this study, we examined how polydatin produces anticancer effects in two types of colon cancer, called HCT116 and HT-29 cells. Polydatin has the ability to repress the progression of colon cancer, and causes a modification of distribution in the cell cycle by a flow cytometry analysis. It also induces mitochondrial dysfunctions through oxidative stress and the loss of mitochondrial membrane potential. The present study investigated the apoptosis caused by the disturbance of calcium regulation and the expression levels of related proteins through flow cytometry and immunoblotting analysis. It was revealed that polydatin suppresses the signaling pathways of the mitogen-activated protein kinase (MAPK) and PI3K/AKT. In addition, it was shown that polydatin combined with 5-FU counteracts drug resistance in 5-FU-resistant cells. Therefore, this study suggests that polydatin has the potential to be developed as an innovative medicinal drug for the treatment of colon cancer.